Single X-ray Projection Material Decomposition using a Mesh Projector - Fleur Linsen; Domenico Iuso; Jan Sijbers (e-Journal of Nondestructive Testing)
This study presents a method for estimating the mass fractions of chemical elements in an object, which is modeled as a homogeneous mixture, using a single X-ray radiograph and its surface mesh. The method assumes that the chemical elements in the mixture and their mass attenuation coefficients are known. A stochastic gradient descent algorithm is used to iteratively minimize the error between a scanned radiograph and a simulated polychromatic radiograph, enabling the estimation of mass fractions. The CAD-ASTRA toolbox is employed to compute the path-lengths and simulate polychromatic X-ray radiographs for test objects under varying noise conditions [1].